A novel method for the design of switching surfaces for discretized MIMO nonlinear systems - Luis-Delgado, José Darío; Al-Hadithi, Basil Mohammed; Jiménez, Agustín (Zielona Góra: Uniwersytet Zielonogórski)
Designing variable structure control with sliding mode (VSC-SM) control schemes needs a switching function or a sliding surface which guarantees the global stability of the closed-loop system. Despite the fact that a wide range of design approaches has been proposed for solving this mathematical problem, the number of proposed methodologies for nonlinear systems is not very extensive, especially for discrete time nonlinear MIMO systems, and most of them require some coordinate system transformation. Therefore, it is not an easy task to find a design scheme that can be applied to discrete time nonlinear MIMO systems.
Keywords: discrete sliding mode; variable structure control (VSC); nonlinear control; optimal control; MIMO systems